The Implementation of KWL (Know, Want to Know, and Learned) to Improve Students’ Reading Comprehension - Agus Sholeh; Novita Elok Rosalina; Riza Weganova, (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis study focused on enhancing students’ reading comprehension through the implementation of K-W-L (know, want to know, and learned) strategy at the secondary level. The purpose of K-W-L strategy is to offer construction for stimulating and building students’ schemata, to create a determination of their reading, and to conclude what they acknowledged before. This research applied Classroom Action Research based on the model suggested by Taggart and Kemmis (1998), consisting of five stages: preliminary study, planning, implementing, observing, and reflecting. The students were asked what they know about the topic, what they wanted to know about the topic and then what they learned from the text after they had read the written text. Based on the findings of the study, this K-W-L strategy trained students to be brave to present in front of the class to share their ideas with their friends, and it also assured other students to keep on listening and appreciating their friends’ comprehension of the text being studied. It is, therefore, strongly suggested that the English teachers at Junior High School use the K-W-L strategy to improve students’ reading comprehension. ABSTRAKPenelitian ini berfokus pada peningkatan pemahaman membaca siswa melalui pengimplementasian strategi KWL (know, want to know, and learned). Tujuan dari strategi KWL ini adalah untuk menstimulasi dan membangun skemata siswa, menciptakan determinasi dalam membaca, dan menggunakan informasi yang telah mereka miliki sebelumnya. Penelitian ini menggunakan penelitian tindakan kelas berdasarkan model yang disarankan oleh Taggart dan Kemmis, yang terdiri darilima tahap, yakni, studi pendahuluan, perencanaan, pengimplementasian, pengobservasian, dan refleksi. Para siswa diberi pertanyaan terkait apa yang mereka ketahui tentang topik tersebut, apa yang mereka ingin ketahui terkait topik tersebut, dan apa yang telah mereka peroleh setelah mereka membaca teks yang diberi. Berdasarkan hasil penelitian, strategi KWL ini melatih siswa untuk memiliki keberanian dalam berekspresi di depan kelas dan membagikan ide dan opini mereka kepada teman-temannya. Selain itu, strategi ini juga melatih siswa untuk mengapresiasi pemahaman yang dimiliki oleh teman yang sedang melakukan presentasi di depan kelas. Oleh karena itu, peneliti menyarankan guru Bahasa inggris di tingkat sekoah menengah pertama untuk menerapkan strategi KWL untuk meningkatkan pemahaman membaca siswa. How to Cite: Sholeh, A., Rosalina, N. E., Weganofa, R. (2020). The Implementation of KWL (Know, Want to Know, and Learned) to Improve Students’ Reading Comprehension. IJEE (Indonesian Journal of English Education), 7(1), 22-31. doi:10.15408/ijee.v7i1.15541